2017
DOI: 10.1515/geoca-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary record of subsidence pulse at the Triassic/Jurassic boundary interval in the Slovenian Basin (eastern Southern Alps)

Abstract: In the Alpine Realm the Early Jurassic is characterized by the disintegration and partial drowning of vast platform areas. In the eastern part of the Southern Alps (present-day NW Slovenia), the Julian Carbonate Platform and the adjacent, E-W extending Slovenian Basin underwent partial disintegration, drowning and deepening from the Pliensbachian on, whereas only nominal environmental changes developed on the large Dinaric (Friuli, Adriatic) Carbonate Platform to the south (structurally part of the Dinarides).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The Krikov Formation from the study area is dominated by hemipelagic limestone, with the subordinate occurrence of resedimented limestones. Similar successions are found in the Mrzli vrh and Mirna sections (Rožič, 2006;Rožič et al, 2017Rožič et al, , 2022, whereas similar developments are found along the entire SB southern margin (Rožič, 2006;Rožič et al, 2019Rožič et al, , 2022.…”
Section: Discussionsupporting
confidence: 61%
“…The Krikov Formation from the study area is dominated by hemipelagic limestone, with the subordinate occurrence of resedimented limestones. Similar successions are found in the Mrzli vrh and Mirna sections (Rožič, 2006;Rožič et al, 2017Rožič et al, , 2022, whereas similar developments are found along the entire SB southern margin (Rožič, 2006;Rožič et al, 2019Rožič et al, , 2022.…”
Section: Discussionsupporting
confidence: 61%
“…3). The succession is generally equal to the one described above in the Geological Setting chapter, but the Norian-Rhaetian is dominated by massive dolomite overlain by basal limestone breccia of the Krikov Formation (for details see Rožič, et al, 2017). Some coarser grained calciturbidites (limestone microbreccia) occur within the Krikov Formation.…”
Section: Mt Mrzli Vrh Sectionmentioning
confidence: 78%
“…This deep basin came into existence between the Adriatic-Dinaridic Carbonate platform (ADCP) and the Julian Carbonate Platform (JCP) in the early Carnian and continued until the Early Cretaceous (Buser 1989;Vrabec et al 2009). The drowning of the JCP took place in the late Pliensbachian and then it was transformed into a submarine high (Rožič et al 2017(Rožič et al , 2018. Since the euphotic conditions did not change significantly on the ADCP, from that time this platform may have been the only source of the redeposited shallow-marine carbonate grains.…”
Section: Comparison With Age-equivalent Successionsmentioning
confidence: 99%